2003
DOI: 10.1083/jcb.200302083
|View full text |Cite
|
Sign up to set email alerts
|

Hrs regulates early endosome fusion by inhibiting formation of an endosomal SNARE complex

Abstract: Movement through the endocytic pathway occurs principally via a series of membrane fusion and fission reactions that allow sorting of molecules to be recycled from those to be degraded. Endosome fusion is dependent on SNARE proteins, although the nature of the proteins involved and their regulation has not been fully elucidated. We found that the endosome-associated hepatocyte responsive serum phosphoprotein (Hrs) inhibited the homotypic fusion of early endosomes. A region of Hrs predicted to form a coiled coi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
100
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 66 publications
7
100
0
1
Order By: Relevance
“…The role of hrs in endosomal recycling is not inconsistent with a hypothesis suggesting that hrs or Vps27p functions in endocytic protein sorting (Katzmann et al, 2001;Bilodeau et al, 2002;Lloyd et al, 2002) and in early endosome fusion (Sun et al, 2003). These studies have suggested that hrs/Vps27p is linked with proteins required for the ubiquitination and sorting of cargo (Katzmann et al, 2001;Bilodeau et al, 2002) and that hrs inhibits homotypic early endosome fusion (Sun et al, 2003).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The role of hrs in endosomal recycling is not inconsistent with a hypothesis suggesting that hrs or Vps27p functions in endocytic protein sorting (Katzmann et al, 2001;Bilodeau et al, 2002;Lloyd et al, 2002) and in early endosome fusion (Sun et al, 2003). These studies have suggested that hrs/Vps27p is linked with proteins required for the ubiquitination and sorting of cargo (Katzmann et al, 2001;Bilodeau et al, 2002) and that hrs inhibits homotypic early endosome fusion (Sun et al, 2003).…”
Section: Discussionmentioning
confidence: 70%
“…The role of hrs in endosomal recycling is not inconsistent with a hypothesis suggesting that hrs or Vps27p functions in endocytic protein sorting (Katzmann et al, 2001;Bilodeau et al, 2002;Lloyd et al, 2002) and in early endosome fusion (Sun et al, 2003). These studies have suggested that hrs/Vps27p is linked with proteins required for the ubiquitination and sorting of cargo (Katzmann et al, 2001;Bilodeau et al, 2002) and that hrs inhibits homotypic early endosome fusion (Sun et al, 2003). Hrs/Vps27p may bind ubiquitinated cargo with its UIM domain (Bilodeau et al, 2002;Polo et al, 2002;Shih et al, 2002), which is required for its cargo sorting function because mutation of that domain blocks sorting of ubiquitinated cargo proteins (Bilodeau et al, 2002;Shih et al, 2002).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Hgs interacts with Eps15, and negatively regulates its function by affecting the interaction of Eps15 with AP2 (Asao et al, 1997;Takata et al, 2000;Bache et al, 2003b). Hgs also binds SNAP25, thereby inhibiting formation of the SNARE complex, and regulating endosomal membrane fusion (Sun et al, 2003), as well as binds a deubiquitylating enzyme, UBPY .…”
Section: The Endocytic Machinery: An Assembly Of Ubiquitinbinding Coamentioning
confidence: 99%